1988
DOI: 10.1002/art.1780310117
|View full text |Cite
|
Sign up to set email alerts
|

Arthritis in idiopathic hypereosinophilic syndrome

Abstract: A 54-year-old man was admitted for tenosynovitis of the wrists, olecranon bursitis, stiffness, progressive flexion of the fingers, subcutaneous nodules, and persistent blood eosinophilia. A high eosinophil count was detected in his synovial fluid. We review the literature on idiopathic hypereosinophilic syndrome. This case provides evidence that nonerosive polyarthritis with periarticular involvement and nodules can be manifestations of this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Martin-Santos et al reported a non-erosive arthropathy with tenosynovitis. 5 Tay CH also reported 10 cases with eosinophilic large joint arthritis of unknown etiology but none had HES. 6 Risk of infection is not high in HES, which explains the culture negative purulent synovitis in this patient; and the high synovial fluid white cells with elevated eosinophils could merely be a representation of a massively high blood leucocytosis and eosinophilia extravasating into the synovial fluid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Martin-Santos et al reported a non-erosive arthropathy with tenosynovitis. 5 Tay CH also reported 10 cases with eosinophilic large joint arthritis of unknown etiology but none had HES. 6 Risk of infection is not high in HES, which explains the culture negative purulent synovitis in this patient; and the high synovial fluid white cells with elevated eosinophils could merely be a representation of a massively high blood leucocytosis and eosinophilia extravasating into the synovial fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Synovial fluid eosinophilia has also been reported in the past. 2,5 Virtually, any organ system may be involved in HES, but the heart, central nervous system, skin, and respiratory tract are commonly involved. Cardiovascular complications of HES are a major source of morbidity and mortality with reported frequency of 40-50%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, parasitic diseases are the most common cause, whereas in developed countries, allergic diseases are the most common cause [7]. Although rheumatologic manifestations of HES are infrequent, several previous reports showed HES association with an inflammatory joint disease mimicking RA [3,[8][9][10]. Furthermore, Tay [11] described 10 patients from Singapore with acute polyarthritis and marked hypereosinophilia of unknown etiology.…”
Section: Discussionmentioning
confidence: 99%